The Prediction of Colorectal Cancer Screening Based on the Extended Parallel Process Model: Moderating the Role of Health Literacy and Cancer-Related Empowerment. - Boogar, Isaac Rahimian; Talepasand, Siavash; Norouzi, Hassan; Mozafari, Sara; Hosseini, Sayed Javad (International Journal of Cancer Management, 2018)
Background: The aim of this study was the prediction of colorectal cancer screening based on the extended parallel processing model regarding the moderating role of cancer-related literacy and cancer-related empowerment. Methods: In a cross sectional survey, 366 participantsamongindividualswhoattended to the specialized internal clinics of Semnan, Iran were selected by convenience sampling. The participants completed the assessment of colon cancer literacy, health education impact questionnaire, colorectal cancer screening questionnaire, colorectal cancer screening decision quality instrument, and demographic checklist. Finally, the data were analyzed with descriptive statistics and structural equation modeling, using SPSS-20 and LISREL 8.8 software. Results: The final model was approved and the model had a good fitness of the data observed. Perceived susceptibility, perceived self-efficacy, and perceived response efficacy indirectly predicted defensive avoidance through cancer-related literacy (P< 0.05). Perceived severity and perceived response efficacy indirectly predicted defensive avoidance through fear of cancer (P < 0.05). Perceived susceptibility and perceived response efficacy indirectly predicted defensive avoidance through health-related empowerment (P < 0.05). In addition, the effect of perceived self-efficacy on the fear of cancer was non-significant (P > 0.05) and perceived severity had a direct effect on the defensive avoidance (P < 0.05). Conclusions: It is concluded that designing the tailored health-promoting programs is crucial to improve perceived self-efficacy, perceived response efficacy, cancer-related literacy, and health-related empowerment for engagement to the colorectal cancer screening. In addition, decreasing or controlling the fear of cancer, perceived susceptibility, and perceived severity, as leading causes of defensive avoidance in colorectal cancer screening, is important.